Do you really need a team? - Kossler, Michael E. (Center for Creative Leadership, 2001)
Despite all of the attention and accolades that organizations place on teams, they are not always the most efficient way to meet a business challenge. It's expensive and time consuming to launch a team, and it's a full-time job to lead a team toward achieving organizational objectives. This guidebook was written to help managers determine if a team is the right tool for meeting a business goal, and explains potential obstacles and challenges to forming a team that can operate at its full potential.
Includes bibliographical references. - Print version record
Keywords: Teams in the workplace; Strategic planning; Work environment; Équipes de travail; Planification stratégique; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; Spanne in die werkplek; Strategiese beplanning; Werksomgewing